Disruption of Tumor Suppressors HNF4α/HNF1α Causes Tumorigenesis in Liver - Aamir Salam Teeli (MDPI AG, 2021)
The hepatocyte nuclear factor-4α (HNF4α) and hepatocyte nuclear factor-1α (HNF1α) are transcription factors that influence the development and maintenance of homeostasis in a variety of tissues, including the liver. As such, disruptions in their transcriptional networks can herald a number of pathologies, such as tumorigenesis. Largely considered tumor suppressants in liver cancer, these transcription factors regulate key events of inflammation, epithelial–mesenchymal transition, metabolic reprogramming, and the differentiation status of the cell. High-throughput analysis of cancer cell genomes has identified a number of hotspot mutations in HNF1α and HNF4α in liver cancer. Such results also showcase HNF1α and HNF4α as important therapeutic targets helping us step into the era of personalized medicine. In this review, we update current findings on the roles of HNF1α and HNF4α in liver cancer development and progression. It covers the molecular mechanisms of HNF1α and HNF4α dysregulation and also highlights the potential of HNF4α as a therapeutic target in liver cancer.